Calix[6]arenes with halogen bond donor groups as selective and efficient anion transporters. Issue 42 (6th May 2022) - Singh, Anurag; Torres-Huerta, Aaron; Vanderlinden, Tom; Renier, Nathan; Martínez-Crespo, Luis; Tumanov, Nikolay; Wouters, Johan; Bartik, Kristin; Jabin, Ivan; Valkenier, Hennie
Abstract : A calix[6]arene with three preorganised halogen bond donating groups gives >100-fold selectivity for Cl −  uniport over HCl symport, in contrast to analogous compounds with strong hydrogen bond donating groups. Abstract : Here we present the anion binding and anion transport properties of a series of calix[6]arenes decorated on their small rim with either halogen bond or hydrogen bond donating groups. We show that the halogen bond donating iodotriazole groups enable highly selective transport of chloride and nitrate anions, without transport of protons or hydroxide, at rates similar to those observed with thiourea or squaramide groups.